2017
DOI: 10.14687/jhs.v14i3.4745
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anxiety on sexual satisfaction in menopausal women

Abstract: Purpose: This study was carried out in order to determine the anxiety levels of menopausal women on their sexual satisfaction. Method and material: This descriptive study. The study was carried out at a menopause clinic of a state hospital between June and August 2011. Data were collected by questionnaire: the Golombok Rust Inventory of Sexual Satisfaction (GRISS) and the State Trait Anxiety Inventory. Results:The mean age of the participants was 49.2±7.6 years old and nearly half of the women 46-50 age group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 14 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Similarly to our findings, in a recent study by Kavlak et al . [ 4 ] sexual satisfaction scores of postmenopausal women were evaluated. The overall and GRISS subscale scores were found to be over 5 except for the communication score (4.7 ±2.4), which supported the presence of sexual dissatisfaction in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to our findings, in a recent study by Kavlak et al . [ 4 ] sexual satisfaction scores of postmenopausal women were evaluated. The overall and GRISS subscale scores were found to be over 5 except for the communication score (4.7 ±2.4), which supported the presence of sexual dissatisfaction in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of factors can be affected by menopause, but among them sexual functions are demonstrated to be influenced the most. However, in the postmenopausal period sexual functions could also be affected, through distinct bio-psychosocial variables such as cultural patterns, religion, menopause duration, personal characteristics, self-esteem, marriage status, feelings and spouse relationship [ 2 - 4 ]. Therefore, evaluation of sexual function in the postmenopausal period is difficult and needs proper understanding and practice to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis showed that the antecedents of the concept of sexual satisfaction in menopause are Individual and background characteristics [ 26 , 31 , 33 35 , 37 , 42 , 43 , 54 , 70 , 71 ], patterns of interpersonal interactions [ 24 , 28 , 34 , 44 , 46 , 47 , 63 , 64 , 71 ], variables related to spouse [ 25 , 34 , 42 , 43 , 52 , 53 , 55 , 60 , 63 , 72 , 80 ], religious and cultural values and beliefs [ 9 , 24 , 30 , 52 , 55 ], and psychological factors [ 1 , 24 , 34 , 38 ], that are explained in the following.…”
Section: Resultsmentioning
confidence: 99%
“…Menopause is a natural biological process that affects women’s lives physically, mentally and sexually [ 1 ]. The global population of postmenopausal women is growing.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is a natural biological process that affects the physical, mental, and sexual life of women [ 1 ]. The WHO predicts that there will be a menopause explosion in 2030, with approximately 1.2 billion women aged over 50 years.…”
Section: Introductionmentioning
confidence: 99%